Comparative Analysis of Cost and Time in the Implementation of Rigid and Flexible Pavement: A Case Study of the Sambeng–Kedewan Road Section, Bojonegoro District - Siswanto; Oetomo, Wateno; Marleno, Risma (Pelopor Publikasi Akademika, 2025)
Road infrastructure plays a crucial role in supporting economic growth, particularly in agrarian and resource-rich regions. This research aims to conduct a comparative analysis of rigid and flexible pavement types in terms of cost efficiency and construction duration on the Sambeng–Kedewan road segment in Bojonegoro Regency. Utilizing the MDPJ 2017 method for flexible pavement design and Pd T-14-2003 for rigid pavement, this research employs a quantitative descriptive-comparative approach to analyze structural thickness, estimated construction costs, and implementation timelines for both 20- and 40-year design life spans. Primary data were collected through field surveys, including Dynamic Cone Penetrometer (DCP) tests for subgrade CBR values, while secondary data were sourced from government agencies and technical literature. Traffic load analysis was performed using ESA5 (Equivalent Standard Axle 5-ton) and JSKN (Number of Commercial Vehicle Axles) parameters, and cost efficiency was evaluated through RAB (Cost Budget Plan) and life cycle cost analysis (LCCA). Findings from various case studies and technical assessments indicate that although rigid pavement involves higher initial investment, it offers greater longevity and lower maintenance expenses in the long term. This research provides crucial insights for local governments in determining the most efficient pavement type under limited budgets and strict construction timeframes. The results are expected to serve as a reference for future infrastructure planning in similar rural and agricultural regions.